PERSEPSI MAHASISWA AKUNTANSI TERHADAP PROFESI AKUNTAN - Amanah Hijriah; Sari Rusmita (ABDI EQUATOR, 2023)
This study aims to be able to provide an overview and information to academics regarding the perceptions of accounting students towards the accounting profession and it is hoped that this can be used as the basis for preparing an accounting curriculum. This research is a field research, which uses primary data in the form of distributing questionnaires to respondents who are students. This study found that 78.3 percent of respondents liked accounting and there were 2.8 percent who did not like accounting, while those who did not show a preference or disapproval of accounting or showed a neutral attitude were as many as 18.8 percent. And there are differences in perceptions between students both based on gender or gender and based on class (senior and junior) regarding the accounting profession.